2010
DOI: 10.1007/s12185-010-0657-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of foscarnet for cytomegalovirus infection after allogeneic hematopoietic stem cell transplantation from a related donor

Abstract: Foscarnet is an active agent against cytomegalovirus (CMV) infection after hematopoietic stem cell transplantation (HSCT), as well as ganciclovir. We investigated the usefulness of foscarnet in patients who underwent related allogeneic HSCT. Foscarnet was used in 320 patients with a median age of 45 years (range 15-72). The purpose of administration was CMV disease in 65, preemptive use in 248 and prophylaxis in 7. Totally, 194 patients had a history of prior ganciclovir treatment. The reason for foscarnet use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…However, published studies of FOS therapy for CMV indicate that resistance has not been described, even at doses lower than the dose our patient received. In 313 HSCT recipients with CMV antigenemia or disease who received FOS for therapy, the median initial FOS dose was 88 mg/kg twice daily and no resistance was reported . Also, no FOS resistance was noted in 110 HSCT recipients with CMV antigenemia treated with FOS 60–90 mg/kg twice daily for 14–28 days , making it unclear if profound immunosuppression or the duration and intensity of FOS exposure played a more significant role in the development of resistance in our patient.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, published studies of FOS therapy for CMV indicate that resistance has not been described, even at doses lower than the dose our patient received. In 313 HSCT recipients with CMV antigenemia or disease who received FOS for therapy, the median initial FOS dose was 88 mg/kg twice daily and no resistance was reported . Also, no FOS resistance was noted in 110 HSCT recipients with CMV antigenemia treated with FOS 60–90 mg/kg twice daily for 14–28 days , making it unclear if profound immunosuppression or the duration and intensity of FOS exposure played a more significant role in the development of resistance in our patient.…”
Section: Discussionmentioning
confidence: 81%
“…The rarity of isolated FOS mutations is, in part, a result of the typical practice of VGCV use preceding the use of FOS. In HSCT recipients, however, the myelosuppressive toxicity of GCV leads to initial use of FOS more commonly than in other populations . Despite this practice, the initial detection of UL54 FOS resistance alone, without UL97 mutations, is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the previous study reported that grade 3/4 electrolyte abnormalities and renal damage associated with foscarnet occurred in 10.9% and 3.4% of the patients. 24 Although considering slight differences in evaluation methods for adverse effects, there appeared no remarkable difference between both results. Therefore, the safety of concomitant use of aerosolized pentamidine in this study was considered to be similar to that of foscarnet monotherapy.…”
Section: Discussionmentioning
confidence: 92%
“…The present study showed that the incidences of grade 3/4 hypocalcemia, hypomagnesemia, and creatinine increase were 9.1%, 6.4%, and 3.6%, respectively, in the non‐pentamidine group. On the other hand, the previous study reported that grade 3/4 electrolyte abnormalities and renal damage associated with foscarnet occurred in 10.9% and 3.4% of the patients . Although considering slight differences in evaluation methods for adverse effects, there appeared no remarkable difference between both results.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence of foscarnet efficacy comes from case series. In one, 313 patients were treated for CMV disease ( n = 65), or were given pre‐emptive therapy of CMV reactivation in related‐ donor transplants ( n = 248) (Asakura et al , ). Of 194 patients had failed previous ganciclovir due to lack of efficacy ( n = 99) or myelosuppression in ( n = 95).…”
Section: Pre‐emptive Therapymentioning
confidence: 99%